Feasibility Analysis of Storage and Renewable Energy Ancillary Services for Grid Operations - Evyatar Littwitz; Ofira Ayalon (Energies)
This study examines the feasibility of deploying renewable energy sources and storage systems to provide ancillary services (ASs), traditionally supplied by conventional power systems, in an electric-island power grid. As renewable energy penetration grows, grid stability becomes increasingly challenged as reduced system inertia and higher variability occur. The study focuses on Israel, which currently lacks operational AS markets. This research explores regulatory, economic, and technical mechanisms to enable renewables and storage systems to provide such services, using a comparative analysis of Germany and California, US, as use cases, along with interview analysis with experts from the Israeli energy sector. The findings highlight, on the one hand, notable regulatory and infrastructural barriers limiting the ability of alternative sources to provide ancillary services. On the other hand, the feasibility and importance of integrating renewables and storage, as regulatory adjustments, market-based procurement mechanisms, and incentive schemes, are to be undertaken. Adopting a structured AS market in Israel, influenced by international best practices, can improve grid resilience, allowing higher renewable integration and supporting long-term energy security and sustainability.